A rare case of aortitis and occlusive iliac thrombus due to Campylobacter fetus bacteremia - Malleswari Ravi; Cristine Arcilla; Gurjit Kaeley (IDCases)
A 66-year-old male presented with 1-week of fever and generalized weakness. Workup revealed Campylobacter fetus bacteremia. Further investigation with imaging showed distal abdominal aortitis with occlusive thrombus in the right common iliac artery. C. fetus bacteremia with endovascular localization is clinically very rare but with high mortality rate.